Pancreatic adenocarcinoma with distant soft tissue metastases: a case report and literature review - Wang, Xiangying; ChangSheng, Yang; Yun, Liu; Xiaodan, Geng (Frontiers in Surgery, 2025)
BackgroundPancreatic cancer is a common malignant tumor that is highly aggressive and can develop distant metastases at an early stage. Pancreatic cancer metastasis often occurs in localized lymph nodes, peritoneum, lungs, and liver. The occurrence of distant soft tissue metastases, especially of skeletal muscles and subcutaneous tissues, is extremely rare. Here, we report a case of pancreatic adenocarcinoma metastatic to the skin of the shoulder.Case reportWe have reported here the case of a middle-aged female patient who was admitted to the hospital with a tumor in her right shoulder and a complaint of severe pain for the past 1 month. After completing the relevant examinations, her tumor was entirely surgically resected, and the postoperative pathological result suggested that the pancreatic adenocarcinoma had metastasized. Next, a computed tomography (CT) scan of the chest, abdomen, and pelvis revealed multiple metastases of pancreatic head cancer. Presently, the patient is at an advanced stage of pancreatic cancer and cannot undergo radical surgery. Accordingly, the patient has been referred to the Department of Gastroenterology for comprehensive treatment. We have discussed this rare case in the light of the literature.ConclusionDistant soft tissue metastasis of pancreatic cancer is extremely rare and is often detected at an advanced stage, thereby showing a poor prognosis. As this cancer can metastasize very fast and is difficult to resect, specific treatment measures must be taken promptly based on the patient's history, symptoms, and clinical manifestations for a comprehensive treatment.